Analisis Keberhasilan Pemasaran Digital UMKM di Indonesia melalui Pendekatan Pluralistik Paul Feyerabend - Dody Kurniawan; Lukman Hakim Sangapan; Robertus Suraji (Fibonacci: Jurnal Ilmu Ekonomi, Manajemen dan Keuangan, 2024)
Digital marketing is an important aspect in the development of MSMEs in Indonesia, especially in the era of rapid digitalization. Although many studies examine digital marketing strategies, there are still limited ones that apply a pluralistic theoretical approach in analyzing the success of MSME digital marketing. This research aims to analyze the success of digital marketing of MSMEs in Indonesia through Paul Feyerabend's pluralistic approach, focusing on understanding the flexibility and diversity of marketing strategies applied by MSME players. The main question to be answered is how MSMEs in Indonesia apply the pluralistic approach in digital marketing and what factors influence its success. This research uses a qualitative design with a case study approach, where data is collected through in-depth interviews with MSME players who have implemented digital marketing. The results show that MSMEs in Indonesia tend to adopt a variety of different digital marketing strategies according to their market characteristics and consumer needs. The pluralistic approach allows flexibility in the use of various digital tools, although the main challenge lies in the limited digital resources and knowledge that are still an obstacle for most MSMEs. The conclusion of this study is that the implementation of digital marketing with a pluralistic approach can improve the marketing effectiveness of MSMEs, but requires further support in terms of education and facilities to maximize the potential of the digital market. The study suggests that MSMEs expand the use of more innovative and flexible digital marketing strategies, and urges the development of further research that examines the role of local context and other external factors.